A Reagent for the One‐Step Preparation of Potassium Acyltrifluoroborates (KATs) from Aryl‐ and Heteroarylhalides1. (30th May 2014) - Erős, Gábor; Kushida, Yo; Bode, Jeffrey W.
Abstract Potassium acyltrifluoroborates (KATs) are fascinating functional groups whose further exploration is limited by poor synthetic access. Documented herein is the design and synthesis of a new reagent for their one‐step preparation from aryl‐ and heteroarylhalides. The reagent is a stable, soluble zwitterion prepared by S‐alkylation of a novel thioformamide trifluoroboronate. The KATs are prepared by adding one equivalent of nBuLi to a mixture of the aryl halide and the reagent at −78 °C. This protocol is suitable for the preparation of KATs containing pyridines, esters, nitro groups, and halides.